Physiological and performance characteristics at maximum intensity freestyle and swimming aids in young swimmers - Beidaris, N.; Platanou, T. (Medicina dello Sport, 2017)
BACKGROUND: Widely known training methods are continuous swimming, intermittent swimming and race swimming. During the training, as a supplementary method, swimming aids (SA) are used in order to help with the development of power and speed. The use of SA during training contributes to greater swimming efficiency by improving specific power of the athlete. The purpose of the present study was to compare maximum intensity between unaided freestyle and freestyle with SA (hand-paddles, pull-buoy, and parachute) into performance and physiological characteristics at 50 and 100 m. METHODS: All the treats had many differences between each other in both performance and physiological characteristics as well as in rate of perceived exertion (RPE). Parachute had the greatest training loads vs. the other treats at mean heart rate at 50 m (169.83±5.65 beat·min-1 vs. 160.55±8.10 hand-paddles, 150.94±9.12 pull-buoy and 169.00±7.84 unaided swimming), and 100 m, respectively (175.22±5.47 beat·min-1 vs. 167.16±6.38 hand-paddles, 154.44±9.53 pull-buoy and 176.16±9.87 unaided swimming). Also parachute had the greatest training loads vs. the other treats at lactate accumulation at 50 m (7.38±2.03 Mmol·l-1 vs. 5.54±1.57 hand-paddles, 4.31±1.81 pull-buoy and 6.86±2.57 unaided swimming) and 100 m respectively (8.62±1.66 Mmol·l-1 vs. 7.05±1.67 hand-paddles, 5.97±2.33 pull-buoy and 7.76±1.89 unaided swimming). RESULTS: Performance and total number of hands mean values had significant differences between parachute and the other treats. Pull-buoy had the least training loads in the physiological characteristics as well as in RPE in both 50 and 100 m distances. CONCLUSIONS: Considering all the above we can note that these findings may help coaches to determine a training schedule.